2020
DOI: 10.3233/jad-190699
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Amyloid-β PET in Atypical Alzheimer’s Disease and Frontotemporal Lobar Degeneration

Abstract: Background: Rates of beta-amyloid (Aβ) accumulation have been characterized across the cognitively normal to typical Alzheimer's dementia spectrum, but little is known about Aβ accumulation in atypical Alzheimer's disease (AD) and other neurodegenerative diseases, such as frontotemporal lobar degeneration (FTLD). We aimed to characterize longitudinal Aβ accumulation, and determine the influence of age, apolipoprotein E genotype, disease duration, and sex in atypical AD and FTLD. Methods: 322 patients (138 atyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…This difference suggested a temporal lag between tau deposition and the progression of neurodegeneration. This assumption has been previously proposed by other studies as well [ 114 , 115 ]. Furthermore, the research found that age has a negative effect on disease progression, since younger patients had higher rates of tau accumulation and atrophy.…”
Section: Contemporary Longitudinal Monitoring Of Ad With Imaging Tsupporting
confidence: 55%
See 1 more Smart Citation
“…This difference suggested a temporal lag between tau deposition and the progression of neurodegeneration. This assumption has been previously proposed by other studies as well [ 114 , 115 ]. Furthermore, the research found that age has a negative effect on disease progression, since younger patients had higher rates of tau accumulation and atrophy.…”
Section: Contemporary Longitudinal Monitoring Of Ad With Imaging Tsupporting
confidence: 55%
“…There is an urgent need for a tool to discover even the smallest Aβ deposits, and cut-off levels need to be defined in order to make studies comparable [ 4 ]. Furthermore, most studies have used radiolabeled tracers in the typical form of the AD spectrum, resulting in much knowledge about Aβ accumulation in typical AD, while the atypical, non-amnestic type has remained understudied [ 115 ]. An increasing body of evidence suggests the utility of Aβ-PET to diagnose patients with atypical manifestations of AD, such as posterior cortical atrophy (PCA) and logopenic-variant primary progressive aphasia (LvPPA) [ 104 , 116 ].…”
Section: Contemporary Early Diagnosis Of Ad With Imaging Techniquementioning
confidence: 99%
“…( Irwin et al, 2015 ) Indeed, while some frontotemporal dementia (FTD) clinical syndromes have group-level statistical associations with one of these proteinopathies, the majority of FTD syndromes do not reliably predict pathology. ( Irwin et al, 2015 , Gorno-Tempini et al, 2011 , Höglinger et al, 2017 , Giannini et al, 2019 , Irwin et al, 2018 , Perry et al, 2017 , Spinelli et al, 2017 ) Moreover, while various degenerative processes can be detected using structural, ( McKiernan and O’Brien, 2017 , McMillan et al, 2014 , Rohrer et al, 2009 , Whitwell et al, 2005 , Whitwell et al, 2015 , Perry et al, 2017 ), diffusion, ( McMillan et al, 2014 , Whitwell et al, 2010 , Illán-Gala et al, 2019 ), and spectroscopic MRI, ( Maul et al, 2020 , Murley et al, 20202020 ), as well as PET, ( Kim et al, 2019 , Whitwell et al, 2020 ); there is currently no method to directly sensitize traditional MRI, or any other in vivo imaging technology, including molecular imaging, to the specific protein inclusions or pathological features that would allow in vivo discrimination of patients with tau and/or TDP-43 inclusions in FTLD. In this report, we explore the novel combination of histopathology and T 2 *-weighted (T2*w) ex vivo 7 T MRI for the purpose of developing a more reliable, data-driven approach to diagnosis of pathology in FTLD spectrum disorders.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study assessing Aβ in 98 individuals with pathologically confirmed frontotemporal dementia syndromes showed that in individuals with various types of frontotemporal dementias, 8%–29% of individuals showed Aβ deposition in the frontotemporal cortexes, and the prevalence increased to 29%–50% if the basal ganglia or substantia nigra were included . Amyloid molecular imaging studies using Pittsburgh Compound B (PiB)-PET scans also revealed amyloid depositions in cortexes and subcortical areas in individuals with FTD. , The coexistence of Aβ and p-tau or other proteinopathies in FTD syndrome, such as TDP-43, fused in sarcoma can be expected; thus, it is unsurprising to observe elevated plasma Aβ 1–42 levels in individuals with FTD. The mean level of plasma Aβ 1–42 is approximately at the level of MCI due to the AD in this study.…”
Section: Results and Discussionmentioning
confidence: 99%